2020
DOI: 10.1002/nafm.10482
|View full text |Cite
|
Sign up to set email alerts
|

Muskellunge Survival, Interbasin Movement, and Emigration in a Simple and a Complex Interconnected Glacial Lake

Abstract: Glacial lakes can display a wide range of morphometries that may affect fish movements and population dynamics. Muskellunge Esox masquinongy is a popular sportfish that is long-lived and occurs at low densities, making population abundance susceptible to sources of fish loss. Yet, factors influencing Muskellunge survival, movement, and emigration in lakes of different morphometric complexities are unknown. We used capture histories of nearly 5,700 individual adult (age ≥ 3; ≥610 mm) Muskellunge collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In our study, weekly estimates of escapement probability ranged from 0.03 with a mean spillway water level of 0.05 m to 0.29 with a spillway level of 0.28 m. Escapement was relatively consistent at water levels up to 0.1 m, after which escapement probability substantially increased. Other studies have found a similar relationship between escapement and discharge (Navarro and McCauley 1993; Weber et al 2013; Weber and Flammang 2019; Meerbeek and Weber 2020), supporting the idea of a discharge threshold that, when passed, leads to dramatic increases in escapement. Armbruster (1962) found that nearly 20,000 Walleye escaped from Berlin Reservoir, Ohio, USA during a 5‐year period, with nearly half of Walleye being mortally wounded during emigration and the majority of escapement occurring during rapid lake level reductions.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, weekly estimates of escapement probability ranged from 0.03 with a mean spillway water level of 0.05 m to 0.29 with a spillway level of 0.28 m. Escapement was relatively consistent at water levels up to 0.1 m, after which escapement probability substantially increased. Other studies have found a similar relationship between escapement and discharge (Navarro and McCauley 1993; Weber et al 2013; Weber and Flammang 2019; Meerbeek and Weber 2020), supporting the idea of a discharge threshold that, when passed, leads to dramatic increases in escapement. Armbruster (1962) found that nearly 20,000 Walleye escaped from Berlin Reservoir, Ohio, USA during a 5‐year period, with nearly half of Walleye being mortally wounded during emigration and the majority of escapement occurring during rapid lake level reductions.…”
Section: Discussionsupporting
confidence: 57%
“…Piscivore assemblages in East Okoboji and West Okoboji lakes include Largemouth Bass, Muskellunge, adult Walleye, Northern Pike, and Smallmouth Bass. Muskellunge and Walleye can move between East Okoboji and West Okoboji lakes, but movement rates between lakes are low (typically <10% annually) and appear to occur primarily in the spring (Meerbeek and Weber 2020; J. Meerbeek, Iowa Department of Natural Resources, unpublished data). Thus, intersystem predator movement was likely low during our fall sampling period.…”
Section: Methodsmentioning
confidence: 99%